Social Media and Tourists’ Decision in Bangladesh: An Empirical Study on Travelling Cox’s Bazar - Faisal-E-ALAM, Md.; MEERO, Abdelrhman; ABDUL RAHMAN, Abdul Aziz; ZAYED, Nurul Mohammad; ISLAM, K. M. Anwarul; IMRAN, Md. Ali (Journal of Environmental Management and Tourism, 2022)
Uses of social media are growing throughout the world. In the previous time, various studies have been directed to discover the necessity of motivational factors behind making decision of tourists. From social media attributes, if tourists have positive insight then they will be inspired to revisit the Cox’s Bazar in future. Also, the tourist industries have given significance to improve their service as part of marketing management to remain competitive. This study identifies the social media attributes and examines the impact of decision making towards travelling Cox’s Bazar. In this study, tourists’ perception of Cox’s Bazar is also found. Foreign tourists (from Asian, European, American, Australian, and African) are considered as sample for this study. Convenience Sampling and questionnaire survey that are taken from various literatures of tourism. Reliability Test and Descriptive Statistics are conducted to see the availability and normality of collected data. Then Demographic Analysis, Spearman’s Rho Correlation Test and finally the Kruskal-Wallis Test have been utilized to find out the relationship among variables. This study discovered that noteworthy impact of social media attributes towards tourists’ choice to travel Cox’s Bazar. These findings will also contribute to the government as the civil aviation and tourism ministry needs to formulate suitable policies and practices considering social media in the existing market for attracting both inbound and outbound tourists.